Electrochemical devices and electronic devices

By setting active layers with different cohesive forces in the electrode sheet of the electrochemical device, the problem of powder loss at the edge of the electrode sheet is solved, the energy density of the electrochemical device is improved and the risk of lithium evolution is reduced.

CN115552657BActive Publication Date: 2025-04-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202180031189.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-10
Publication Date
2025-04-25
Estimated Expiration
2041-08-10

AI Technical Summary

Technical Problem

In electrochemical devices, the active material layer at the edge of the electrode sheet is prone to loosening and powder loss, which makes it difficult to increase the energy density of the electrode sheet and there is a risk of lithium extraction.

Method used

By providing the first active layer and the second active layer in the electrode sheet, the cohesion force of the first active layer is greater than the cohesion force of the second active layer, ensuring that the edges of the electrode sheet are not prone to powder loss, thereby allowing the compaction density of the electrode sheet to be further improved.

Benefits of technology

The volume energy density of the electrochemical device is improved, the risk of lithium extraction is reduced, and the adhesion of the edges of the electrode sheet is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115552657B_ABST
    Figure CN115552657B_ABST
Patent Text Reader

Abstract

The present application provides an electrochemical device and an electronic device. The electrochemical device includes a first pole piece, a second pole piece having electrical properties different from the first pole piece, and an isolation membrane disposed between the first pole piece and the second pole piece. The first pole piece includes a current collector, a pole ear, and an active layer. The pole ear is electrically connected to the current collector and extends out of the current collector. The active layer is disposed on the surface of the current collector, and the active layer includes a first active layer and a second active layer. Along the first direction, the first active layer is located on the side of the second active layer facing the pole ear, and is adjacent to or partially overlaps with the second active layer. Along the second direction, the first active layer and the second active layer extend in a strip shape. The cohesive force of the first active layer is greater than the cohesive force of the second active layer. By making the cohesive force of the first active layer greater than the cohesive force of the second active layer, the first pole piece is less likely to have edge powdering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to electrochemical devices and electronic devices. Background Art

[0002] The volume energy density of electrochemical devices (e.g., lithium-ion batteries) has always been a bottleneck restricting the development of electrochemical devices. In order to improve the volume energy density of electrochemical devices, it is usually necessary to increase the compaction density of the pole piece. However, under the condition of increasing the compaction density of the pole piece, due to the higher pressure, the active material layer at the edge of the pole piece is prone to loosening and powdering, which is not conducive to improving the energy density of the pole piece and may cause the risk of lithium precipitation. Therefore, further improvements are expected. Summary of the invention

[0003] Some embodiments of the present application provide an electrochemical device, which includes a first pole piece, a second pole piece with electrical properties different from the first pole piece, and an isolation membrane arranged between the first pole piece and the second pole piece. The first pole piece includes a current collector, a pole ear and an active layer, and the pole ear is electrically connected to the current collector and extends from the current collector. The active layer is arranged on the surface of the current collector, and the active layer includes a first active layer and a second active layer. Along the first direction, the first active layer is located on the side of the second active layer facing the pole ear, and is adjacent to or partially overlaps with the second active layer. Along the second direction, the first active layer and the second active layer are extended in a strip shape. The cohesive force of the first active layer is greater than the cohesive force of the second active layer. In a three-dimensional rectangular coordinate system, the first direction is the direction in which the pole ear extends out of the current collector, the third direction is the thickness direction of the negative electrode pole piece, and the second direction is perpendicular to the plane where the first direction and the second direction are located.

[0004] The present application makes the cohesive force of the first active layer greater than the cohesive force of the second active layer, so that powder loss is less likely to occur at the edge of the electrode, thereby allowing the compaction density of the electrode to be further improved, thereby increasing the volume energy density of the electrochemical device and reducing the risk of lithium plating.

[0005] In some embodiments, the cohesive force of the first active layer is 10 N / m to 20 N / m, and the cohesive force of the second active layer is 4 N / m to 8 N / m. Within this range, the powder falling phenomenon at the edge of the pole piece can be significantly improved, and it will not have an adverse effect on the conductivity of the pole piece and the energy density of the electrochemical device.

[0006] In some embodiments, the width of the first active layer is 5 mm to 20 mm, and the width of the second active layer is 10 mm to 300 mm.

[0007] In some embodiments, the bonding force between the first active layer and the current collector is greater than the bonding force between the second active layer and the current collector. In this way, the bonding between the active layer at the edge of the pole piece and the current collector is better and it is less likely to fall off from the current collector.

[0008] In some embodiments, the bonding force between the first active layer and the current collector is 8 N / m to 20 N / m, and the bonding force between the second active layer and the current collector is 1 N / m to 8 N / m.

[0009] In some embodiments, the first active layer includes a first active material and a first binder, the second active layer includes a second active material and a second binder, and the powder compaction density of the first active material is greater than the powder compaction density of the second active material. By increasing the powder compaction density of the first active material at the edge of the pole piece, its coating weight per unit area can be increased, which can not only improve the powder falling phenomenon at the edge of the pole piece, but also improve the energy density of the electrochemical device.

[0010] In some embodiments, the first active layer includes a first active material and a first binder, the second active layer includes a second active material and a second binder, and the mass fraction of the first binder in the first active layer is greater than the mass fraction of the second binder in the second active layer. A higher binder content can increase the bonding between active material particles and improve the powder falling phenomenon at the edge of the pole piece.

[0011] In some embodiments, the first active layer includes a first active material and a first binder, the second active layer includes a second active material and a second binder, the powder compaction density of the first active material is greater than the powder compaction density of the second active material, and the mass fraction of the first binder in the first active layer is greater than the mass fraction of the second binder in the second active layer. The powder compaction density of the active material in the first active layer and the content of the binder are increased to further improve the powder falling phenomenon at the edge of the pole piece.

[0012] In some embodiments, the powder compaction density of the first active material is 1.8 g / cm 3 Up to 2.5g / cm 3 The compacted density of the second active material powder is 1 g / cm 3 Up to 1.7g / cm 3 .

[0013] In some embodiments, the mass fraction of the first binder in the first active layer is 15% to 30%, and the mass fraction of the second binder in the second active layer is 1% to 10%.

[0014] In some embodiments, the powder compaction density of the first active material is 1.8 g / cm 3 Up to 2.5g / cm 3The compacted density of the second active material powder is 1 g / cm 3 Up to 1.7g / cm 3 The mass fraction of the first binder in the first active layer is 15% to 30%, and the mass fraction of the second binder in the second active layer is 1% to 10%.

[0015] In some embodiments, the first active material and the second active material each independently include at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composites, silicon oxides, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, lithium titanate, Li-Al alloys, or metallic lithium.

[0016] In some embodiments, the first binder and the second binder each independently include at least one of polypropylene alcohol, polyacrylic acid, polyacrylate, polyimide, polyamideimide, styrene-butadiene rubber, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, aqueous acrylic resin or carboxymethyl cellulose salt.

[0017] In some embodiments, the tabs are integrally formed with the current collector.

[0018] An embodiment of the present application further provides an electronic device, comprising the above-mentioned electrochemical device.

[0019] The embodiments of the present application make the cohesive force of the first active layer greater than the cohesive force of the second active layer, so that the edge of the electrode is less likely to lose powder, which can allow the compaction density of the electrode to be further improved, thereby improving the volume energy density of the electrochemical device and reducing the risk of lithium plating. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A top view of a first pole piece of some embodiments of the present application is shown;

[0021] Figure 2 Shows Figure 1 The cross-sectional view of the first pole piece along the AA' direction is shown. DETAILED DESCRIPTION

[0022] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.

[0023] Some embodiments of the present application provide an electrochemical device, which includes a first pole piece, a second pole piece, and an isolation membrane disposed between the first pole piece and the second pole piece, wherein the first pole piece and the second pole piece have different electrical properties.

[0024] In some embodiments, the first pole piece includes a current collector, a pole tab and an active layer, the pole tab is electrically connected to the current collector and extends out of the current collector, and the active layer is disposed on the surface of the current collector.

[0025] In some embodiments, the active layer is disposed on one side surface of the current collector, and in other embodiments, the active layer is disposed on both sides surface of the current collector.

[0026] like Figure 1 , which shows a top view of the first pole piece in an unfolded state in some embodiments. Figure 2 As shown, it is shown Figure 1 The cross-sectional view of the first pole piece along the AA' direction is shown. Figure 1 and Figure 2 , the active layer 102 is disposed on both sides of the current collector 101, and the active layer 102 includes a first active layer 1021 and a second active layer 1022. Figure 1 As shown, along the first direction x, the first active layer 1021 is located on the side of the second active layer 1022 facing the electrode ear 103 (that is, along the first direction, the first active layer 1021 is closer to the side of the current collector extending out of the electrode ear than the second active layer 1022), and is adjacent to or partially overlapped with the second active layer 1022; along the second direction y, the first active layer 1021 and the second active layer 1022 extend in a strip shape, as shown in FIG. Figure 1 As shown, the first active layer 1021 and the second active layer 1022 are both rectangular strips and extend parallel to each other along the second direction y.

[0027] In the present application, the above directions are defined as follows: in a three-dimensional rectangular coordinate system, the first direction x is the direction in which the pole ear extends out of the current collector, the third direction z is the thickness direction of the first pole piece, and the second direction y is perpendicular to the plane where the first direction x and the third direction z are located.

[0028] It should be understood that the above-mentioned “adjacent” means that the first active layer 1021 and the second active layer 1022 do not overlap in the third direction z (i.e., the thickness direction of the electrode piece) and are not spaced in the first direction x (i.e., the direction in which the electrode ear extends out of the current collector). In this way, it is possible to prevent the contact area between the first active layer 1021 and the second active layer 1022 from being too thick, thereby affecting the local thickness of the electrode piece and adversely affecting the flatness of the battery cell. The above-mentioned “partial overlap” means that along the third direction z (i.e., the thickness direction of the electrode piece), the projected area of ​​the first active layer 1021 and the second active layer 1022 on the current collector has an overlapping area, that is, on the surface of the current collector, in the contact area between the first active layer and the second active layer, the first active layer 1021 may be superimposed on the second active layer 1022, or the second active layer 1022 may be superimposed on the first active layer 1021.

[0029] Usually, in the coating process of preparing the pole piece, a metal foil is selected as the current collector, and the active slurry is coated on the surface of the metal foil. There will be a coating area coated with the active slurry and an empty foil area not coated with the active slurry on the surface of the metal foil. The empty foil area can be used to die-cut the pole lugs or weld the pole lugs. In order to improve the energy density of the battery, before the coated foil is cut into pole pieces, the coated area needs to be compacted to increase the coating weight per unit area, that is, to increase the compaction density of the active material layer. Because at the edge of the coating area, that is, on the side of the coating area close to the empty foil area, the active material layer will be easily loosened due to the vertical stress of the compaction process, and powdering will occur. The occurrence of powdering will cause the coating weight per unit area at the edge of the pole piece after cutting to decrease, thereby reducing the energy density of the battery and posing the risk of lithium precipitation.

[0030] In the present application, in the coating process, two different first active slurries and second active slurries are respectively coated on the surface of the metal foil, forming a first coating area coated with the first active slurry and a second coating area coated with the second active slurry, and the first coating area is located on the side of the second coating area close to the empty foil area, that is, the first active layer 1021 is set at the edge of the second active layer 1022, and the cohesion of the first active layer 1021 is greater than the cohesion of the second active layer 1022. During the compaction process, the first active layer 1021 is not easy to loosen due to its greater cohesion, which reduces the occurrence of edge powdering. Therefore, on the prepared pole piece, the edge of the pole piece has a unit area coating weight equivalent to that of the middle of the pole piece, which is beneficial to the improvement of the energy density of the electrochemical device. At the same time, due to the reduction in the possibility of edge powdering, the compaction density of the pole piece can be further improved, thereby improving the volume energy density of the electrochemical device.

[0031] In some embodiments, the cohesion of the first active layer is 10N / m to 20N / m, and the cohesion of the second active layer is 4N / m to 8N / m. If the cohesion of the first active layer is too small, the effect on improving the powder falling off at the edge of the first electrode is relatively limited; if the cohesion of the first active layer is too large, it is usually required that the compaction density of the active layer is too large or more binders are used. Excessive compaction density is likely to affect the penetration of the electrolyte and the conductivity of the electrode; and using more binders means reducing the amount of active materials, affecting the conductivity of the electrode and the energy density of the electrochemical device. In some embodiments, the cohesion of the first active layer is 10N / m, 12N / m, 15N / m, 18N / m, 20N / m, or in the range of any two of the above values. In some embodiments, the cohesion of the second active layer is 4N / m, 6N / m, 8N / m, or in the range of any two of the above values.

[0032] In some embodiments, the width of the first active layer is 5 mm to 20 mm, and the width of the second active layer is 10 mm to 300 mm. If the width of the first active layer is too small, its effect on improving the edge powdering of the pole piece is relatively limited; if the width of the first active layer is too large, when the content of the binder in the first active layer is high, it will have an adverse effect on the volume energy density of the electrochemical device. In some embodiments, the width of the first active layer is 5 mm, 12 mm, 15 mm, 18 mm, 20 mm, or in a range consisting of any two of the above values. In some embodiments, the width of the second active layer is 10 mm, 30 mm, 50 mm, 80 mm, 100 mm, 120 mm, 150 mm, 180 mm, 300 mm, or in a range consisting of any two of the above values.

[0033] In some embodiments, the bonding force between the first active layer and the current collector is greater than the bonding force between the second active layer and the current collector, so that the first active layer is less likely to fall off from the current collector, and the effect of improving the edge powdering of the electrode piece is more stable.

[0034] In some embodiments, the bonding force between the first active layer and the current collector is 8N / m to 20N / m, and the bonding force between the second active layer and the current collector is 1N / m to 8N / m. If the bonding force between the first active layer and the current collector is too small, the first active layer is easy to fall off from the current collector, thereby affecting the first active layer's role in improving the powder loss at the edge of the pole piece; if the bonding force between the first active layer and the current collector is too large, a higher binder content in the first active layer is usually required, which is not conducive to improving the volume energy density of the electrochemical device. In some embodiments, the bonding force between the first active layer and the current collector is 8N / m, 10N / m, 12N / m, 15N / m, 18N / m, 20N / m, or in the range of any two of the above values. In some embodiments, the bonding force between the second active layer and the current collector is 1N / m, 3N / m, 5N / m, 6N / m, 8N / m, or in the range of any two of the above values.

[0035] In some embodiments, the first active layer includes a first active material and a first binder, the second active layer includes a second active material and a second binder, and the powder compaction density of the first active material is greater than the powder compaction density of the second active material. The greater the powder compaction density, the higher the weight of the active material per unit volume using the same pressure. Therefore, when compacting, under the same cold pressing conditions, since the first active material located at the edge of the pole piece has a higher powder compaction density, the edge of the pole piece will not lose powder because it can accommodate more of the first active material. Under this condition, the pressure during the compaction process can be increased. When the pressure increases, the pole piece will not lose powder at the edge, thereby increasing the coating weight per unit area, and the compaction density of the pole piece is improved, which is beneficial to increase the energy density of the electrochemical device.

[0036] In some embodiments, the mass fraction of the first binder in the first active layer is greater than the mass fraction of the second binder in the second active layer. By making the mass fraction of the first binder in the first active layer greater than the mass fraction of the second binder in the second active layer, more binder will allow the active material particles to have better bonding with each other, and the cohesive force of the first active layer can be greater than the cohesive force of the second active layer.

[0037] In some embodiments, the powder compaction density of the first active material is 1.8 g / cm 3 Up to 2.5g / cm 3 The compacted density of the second active material powder is 1 g / cm 3 Up to 1.7g / cm 3 By making the powder compaction density of the first active material greater than 1.8 g / cm 3 , can improve the edge powdering phenomenon of the pole piece; however, when the compaction density of the powder of the first active material is too large, for example, greater than 2.5g / cm 3 , which may be detrimental to the infiltration of the electrolyte. In some embodiments, the compacted density of the first active material powder is 1.8 g / cm 3 , 2.0g / cm 3 , 2.2g / cm 3 , 2.5g / cm 3 Or in the range formed by any two of the above values. In some embodiments, the powder compaction density of the second active material is 1 g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 , 1.7g / cm 3 Or the range consisting of any two of the above values.

[0038] In some embodiments, the mass fraction of the first binder in the first active layer is 15% to 30%, and the mass fraction of the second binder in the second active layer is 1% to 10%. If the mass fraction of the first binder in the first active layer is too small, it is not conducive to improving the cohesion of the first active layer, and the effect of improving the edge powder loss of the electrode sheet is relatively limited; if the mass fraction of the first binder in the first active layer is too large, it is not conducive to improving the volumetric energy density of the electrochemical device. In some embodiments, the mass fraction of the first binder in the first active layer is 15%, 20%, 25%, 30% or within the range composed of any two of the above values. In some embodiments, the mass fraction of the second binder in the second active layer is 1%, 3%, 5%, 8%, 10% or within the range composed of any two of the above values.

[0039] In some embodiments, the first electrode sheet is a negative electrode sheet, the active layer is a negative electrode active layer, the current collector is a negative electrode current collector, and the negative electrode current collector can be at least one of copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, composite current collector or carbon-based current collector. Correspondingly, the second electrode sheet is a positive electrode sheet. By improving the edge powder loss phenomenon of the negative electrode sheet, the coating weight per unit area of the negative electrode active material at the edge of the electrode sheet can be increased, providing more positions for the insertion and extraction of lithium ions, thereby reducing the risk of lithium deposition at the edge of the negative electrode sheet and being beneficial to improving the energy density of the electrochemical device.

[0040] In some embodiments, the first active material and the second active material each independently include at least one of natural graphite, artificial graphite, mesophase microcarbon spheres, hard carbon, soft carbon, silicon, silicon-carbon composite, silicon oxide (such as SiO x (0 < x < 2)), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithium titanate, Li-Al alloy or metallic lithium.

[0041] In some embodiments, the first electrode sheet is a positive electrode sheet, the active layer is a positive electrode active layer, the current collector is a positive electrode current collector, and the positive electrode current collector includes aluminum foil. Correspondingly, the second electrode sheet is a negative electrode sheet. By improving the edge powder loss phenomenon of the positive electrode sheet, the coating weight per unit area of the positive electrode active material at the edge of the electrode sheet can be increased, increasing the number of lithium ions, and thus being beneficial to increasing the energy density of the electrochemical device.

[0042] In some embodiments, the first active material and the second active material each independently include at least one of lithium cobaltate, lithium iron phosphate, lithium manganese iron phosphate, sodium iron phosphate, lithium vanadium phosphate, sodium vanadium phosphate, lithium vanadium oxide phosphate, sodium vanadium oxide phosphate, lithium vanadate, lithium manganate, lithium nickelate, lithium nickel cobalt manganate, lithium-rich manganese-based material or lithium nickel cobalt aluminate.

[0043] In some embodiments, the first binder and the second binder each independently include at least one of polypropylene alcohol, polyacrylic acid, polyacrylate, polyimide, polyamideimide, styrene-butadiene rubber, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, aqueous acrylic resin or carboxymethyl cellulose salt.

[0044] In some embodiments, the first active layer and the second active layer each further include a conductive agent. In some embodiments, the conductive agent includes at least one of conductive carbon black, Ketjen black, flake graphite, graphene, carbon nanotubes, or carbon fibers.

[0045] In some embodiments, the tabs are integrally formed with the current collector 101. This is beneficial to simplify the preparation process of the electrochemical device and also beneficial to the stable connection of the tabs.

[0046] In some embodiments, the electrochemical device may further include an electrolyte, which may be at least one of a gel electrolyte, a solid electrolyte, and an electrolyte. In some embodiments, the electrolyte includes a lithium salt and a non-aqueous solvent. In some embodiments, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, or lithium difluoroborate. The non-aqueous solvent may be at least one of a carbonate compound, a carboxylate compound, an ether compound, or other organic solvents.

[0047] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect.

[0048] In some embodiments, the surface of the isolation membrane may further include a porous layer, which is disposed on at least one surface of the isolation membrane, and the porous layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The porous layer on the surface of the isolation membrane can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece.

[0049] In some embodiments of the present application, the first pole piece, the separator and the second pole piece are stacked and then wound to obtain a wound electrode assembly, thereby preparing an electrochemical device. In some embodiments, the first pole piece, the separator and the second pole piece are stacked to obtain a laminated electrode assembly, thereby preparing an electrochemical device.

[0050] In some embodiments, the electrochemical device includes a lithium-ion battery, but the application is not limited thereto.

[0051] In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode sheet, a separator, and a negative electrode sheet are prepared into a wound electrode assembly, which is then packaged in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and packaged to produce a lithium-ion battery. Then, the prepared lithium-ion battery is subjected to a performance test.

[0052] Those skilled in the art will appreciate that the above-described method for preparing an electrochemical device (eg, a lithium-ion battery) is only an example, and other methods commonly used in the art may be used without departing from the disclosure of the present application.

[0053] Embodiments of the present application also provide electronic devices including the above-mentioned electrochemical devices. The electronic devices of the embodiments of the present application are not particularly limited, and they can be any electronic devices known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.

[0054] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.

[0055] Example 1

[0056] Preparation of positive electrode sheet: Mix the positive electrode active materials lithium cobalt oxide, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) in a weight ratio of 97:1.4:1.6, add N-methylpyrrolidone (NMP) as a solvent, and stir evenly. The slurry (solid content of 72wt%) is evenly coated on the positive electrode current collector aluminum foil with a coating thickness of 80μm, dried at 85℃, and then cold pressed, cut, and slit, and dried under vacuum conditions at 85℃ for 4 hours to obtain the positive electrode sheet.

[0057] Preparation of negative electrode sheet: Add water to negative electrode active material natural graphite, dispersant lithium carboxymethyl cellulose, and binder polyacrylic acid at a weight ratio of 8:0.2:1.8 and stir until the slurry is evenly dispersed to obtain the first slurry. Add water to negative electrode active material natural graphite, dispersant lithium carboxymethyl cellulose, and binder polyacrylic acid at a weight ratio of 9:0.2:0.8 and stir until the slurry is evenly dispersed to obtain the second slurry. A 10 μm thick copper foil is used as the negative electrode current collector. A zebra coating process (i.e., interval coating) is adopted to respectively coat the first slurry and the second slurry on the surface of the negative electrode current collector to form a coating area, and an empty foil area not coated with the first slurry and the second slurry is exposed. The first slurry is located on the side of the second slurry close to the empty foil area, that is, the second slurry is located at the edge of the coating area. The coating thickness is 50 μm. It is dried at 85°C, and then after cold pressing, cutting, and slitting, the empty foil area is die-cut to obtain a pole ear. Further, it is dried under vacuum conditions at 120°C for 12 hours to obtain a negative electrode sheet.

[0058] Preparation of isolation film: The isolation film is 7 μm thick polyethylene (PE).

[0059] Preparation of electrolyte: In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) were mixed in a mass ratio of EC: PC: DEC = 1:1:1, dissolved and stirred thoroughly, then lithium salt LiPF6 was added and mixed evenly to obtain an electrolyte in which the concentration of LiPF6 was 1 mol / L.

[0060] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, trimming, etc.

[0061] Other embodiments and comparative examples are based on the steps of embodiment 1 with parameter changes, and the specific changed parameters are as follows.

[0062] The difference between Example 2 and Example 1 is only the composition of the first slurry, which is: the weight ratio of natural graphite, dispersant lithium carboxymethyl cellulose, and adhesive polyacrylic acid is 7.8:0.2:2.

[0063] The difference between Example 3 and Example 1 is only in the composition of the first slurry, where the weight ratio of natural graphite, dispersant lithium carboxymethyl cellulose, and adhesive polyacrylic acid is 7.6:0.2:2.2.

[0064] The difference between Example 4 and Example 1 is that the dispersant in the second slurry is sodium carboxymethyl cellulose and the binder is styrene-butadiene rubber; in addition, the composition of the first slurry is different, namely, the weight ratio of artificial graphite, dispersant sodium carboxymethyl cellulose, and binder styrene-butadiene rubber is 9:0.2:0.8, and the compacted density of the artificial graphite powder is 1.85 g / cm 3 .

[0065] The only difference between Example 5 and Example 4 is that the compacted density of the artificial graphite powder is 1.95 g / cm 3 .

[0066] The only difference between Example 6 and Example 4 is that the compacted density of the artificial graphite powder is 2 g / cm 3 .

[0067] The difference between Example 7 and Example 1 is that the composition of the first slurry is different, namely, the weight ratio of artificial graphite, dispersant sodium carboxymethyl cellulose, and adhesive styrene-butadiene rubber is 8:0.2:1.8, and the compacted density of the artificial graphite powder is 1.85 g / cm 3 .

[0068] The difference between Example 8 and Example 7 is that the compacted density of the artificial graphite powder is 2 g / cm 3 .

[0069] In Comparative Example 1, only the second slurry is coated on the negative electrode current collector, and the first slurry is not coated, so that the composition of the second slurry is: the weight ratio of natural graphite, dispersant sodium carboxymethyl cellulose, and adhesive styrene butadiene rubber is 9:0.2:0.8, and the compacted density of the artificial graphite powder is 1.65g / cm 3 .

[0070] The difference between Comparative Example 2 and Comparative Example 1 is that the active material of the second slurry is changed from natural graphite to hard carbon, and the compacted density of the hard carbon powder is 1.2 g / cm 3 The difference between Comparative Example 3 and Comparative Example 1 is that the binder in the second slurry is changed from styrene-butadiene rubber to sodium polyacrylate.

[0071] The test methods for various parameters of this application are described below.

[0072] 1. Test of the bonding strength between the negative electrode active layer and the negative electrode current collector:

[0073] The brand of the instrument used for testing the adhesion between the negative electrode active layer and the negative electrode current collector is Instron, model 33652. Take the negative electrode (width 30mm×length (100mm to 160mm)), fix it on the steel plate with double-sided tape (model: 3M9448A, width 20mm×length (90mm to 150mm)), fix a paper tape with the same width as the negative electrode to one side of the negative electrode with tape, adjust the limit block of the tensile testing machine to the appropriate position, fold the paper tape upward and slide 40mm, the sliding rate is 50mm / min, and test the adhesion between the negative electrode active layer and the negative electrode current collector at 180° (i.e., stretching in the opposite direction).

[0074] 2. Cohesion test method:

[0075] Take the dried electrode and use a blade to cut a sample with a width of 30mm × length (100mm to 160mm). Stick the special double-sided tape on the steel plate, the tape width is 20mm × length (90mm to 150mm). Stick the electrode sample on the double-sided tape with the test side facing down. Then stick the green glue (width 20mm × length (90mm to 150mm) close to the surface of the electrode. Insert a paper tape with a width equal to the electrode and a length greater than the sample length of 80mm to 200mm under the green glue and fix it with wrinkled glue. Turn on the power of the Sansi tensile testing machine, the indicator light is on, adjust the limit block to the appropriate position, fold the green glue upward and slide 40mm, the sliding rate is 50mm / min, and test the cohesion between the negative active layers at 180° (i.e. stretching in the opposite direction).

[0076] 3. Powder compaction density test

[0077] The powder is scraped from the electrode and sintered to obtain the active material powder, which is placed in the powder density tester mold (test mold (CARVER#3619 (13mm)); the test equipment is Sansi Zongheng UTM7305, the mold is placed in the middle of the upper and lower pressure plates of the equipment, click the run button in the equipment, the equipment will run according to the set parameters, and when the pressure is released from the equipment pressure point to 5T, the displacement value at this time is recorded, which is the thickness of the sample under this pressure (the pressure increase rate is 10mm / min, the pressure increase holding time is 30s, the pressure relief rate is 30mm / min, and the pressure relief holding time is 10s). Among them, the compacted density of the powder can be calculated by the following formula:

[0078] ρc=m / V=m / S*H,

[0079] Where: ρc-----compression density of powder, g / cm3;

[0080] m-----weigh the mass of the material, g;

[0081] S-----Mold bottom area, cm2;

[0082] H-----height after compaction, cm.

[0083] 4. Adhesive content test method

[0084] Scrape the powder from the electrode and place the powder in a thermogravimetric tester. Set the temperature range to 20-500°C, the heating rate to 5°C / min, the gas atmosphere to air, and then run the equipment at a temperature between 200 and 400°C until the weight decreases. The weight percentage of the reduced weight is the adhesive content.

[0085] Table 1 shows the respective parameters and evaluation results of the corresponding Examples 1 to 8 and Comparative Examples 1 to 3.

[0086]

[0087]

[0088] By comparing Example 4 and Comparative Example 1, it can be seen that, compared with the negative electrode sheet containing only the second active layer, by providing an additional first active layer and making the cohesive force of the first active layer greater than the cohesive force of the second active layer, the edge powder falling of the negative electrode sheet can be significantly improved.

[0089] By comparing Examples 1 to 3, it can be seen that when the active materials in the first active layer are the same, as the amount of binder in the first active layer increases, the cohesion and adhesion of the first active layer increase, and the negative electrode sheet hardly loses powder.

[0090] By comparing Examples 4 to 6, it can be seen that when the contents of the components in the first active layer are the same, the greater the powder compaction density of the first active material in the first active layer, the greater the cohesion and adhesion, and the negative electrode plate hardly loses powder.

[0091] By comparing Examples 1-6 and Examples 7-8, it can be seen that the greater the compaction density of the powder of the first active material in the first active layer, the greater the amount of binder used, the greater the cohesive force and the adhesive force will be, and at this time the negative electrode sheet will not lose powder.

[0092] In Comparative Examples 1-3, when the same active layer is set in the middle and edge of the current collector, obvious powder loss will occur. In Comparative Example 2, relative to Comparative Example 1, when the type of active material and the powder compaction density of the first active layer are changed, obvious powder loss will still occur. In Comparative Example 3, relative to Comparative Example 1, when the binder in the first active layer is changed, obvious powder loss will still occur. It can be seen that when the powder compaction density of the first active material is low and the amount of binder in the first active is small, the edge of the pole piece is prone to powder loss.

[0093] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.

Claims

1. An electrochemical device, comprising a first pole piece, a second pole piece having electrical properties different from the first pole piece, and a separator disposed between the first pole piece and the second pole piece, wherein: The first pole piece comprises: current collector; A tab, electrically connected to the current collector and extending from the current collector; An active layer is arranged on the surface of the current collector, the active layer includes a first active layer and a second active layer, along the first direction, the first active layer is located on the side of the second active layer facing the electrode ear, and is adjacent to or partially overlapped with the second active layer, along the second direction, the first active layer and the second active layer are extended in a strip shape; wherein the cohesive force of the first active layer is greater than the cohesive force of the second active layer; In a three-dimensional rectangular coordinate system, the first direction is the direction in which the pole ear extends out of the current collector, the third direction is the thickness direction of the first pole piece, and the second direction is perpendicular to the plane where the first direction and the third direction are located; The first active layer includes a first active material and a first binder, the second active layer includes a second active material and a second binder, and the powder compaction density of the first active material is greater than the powder compaction density of the second active material.

2. The electrochemical device according to claim 1, wherein: The cohesive force of the first active layer is 10 N / m to 20 N / m, and the cohesive force of the second active layer is 4 N / m to 8 N / m.

3. The electrochemical device according to claim 1, wherein The width of the first active layer is 5 mm to 20 mm, and the width of the second active layer is 10 mm to 300 mm.

4. The electrochemical device according to claim 1, wherein The bonding force between the first active layer and the current collector is greater than the bonding force between the second active layer and the current collector.

5. The electrochemical device according to claim 1, wherein The bonding force between the first active layer and the current collector is 8 N / m to 20 N / m, and the bonding force between the second active layer and the current collector is 1 N / m to 8 N / m.

6. The electrochemical device according to claim 1, wherein The mass fraction of the first binder in the first active layer is greater than the mass fraction of the second binder in the second active layer.

7. The electrochemical device according to claim 6, wherein: The powder compaction density of the first active material is 1.8 g / cm 3 Up to 2.5g / cm 3 The powder compaction density of the second active material is 1g / cm 3 Up to 1.7g / cm 3 , and / or, the mass fraction of the first binder in the first active layer is 15% to 30%, and the mass fraction of the second binder in the second active layer is 1% to 10%.

8. The electrochemical device according to claim 6, wherein: The first active material and the second active material each independently include at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, silicon oxide, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithium titanate, Li-Al alloy or metallic lithium; the first binder and the second binder each independently include at least one of polypropylene alcohol, polyacrylic acid, polyacrylic acid salt, polyimide, polyamide-imide, styrene-butadiene rubber, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, aqueous acrylic resin or carboxymethyl cellulose salt.

9. The electrochemical device according to claim 1, wherein: The pole ear and the current collector are integrally formed.

10. An electronic device comprising the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium battery pole sheet and preparation method thereof

    CN110137434A